2023
DOI: 10.1007/s00221-023-06679-6
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoneglect during object search in naturalistic scenes

Antje Nuthmann,
Christopher N. L. Clark

Abstract: Pseudoneglect, that is the tendency to pay more attention to the left side of space, is typically assessed with paper-and-pencil tasks, particularly line bisection. In the present study, we used an everyday task with more complex stimuli. Subjects’ task was to look for pre-specified objects in images of real-world scenes. In half of the scenes, the search object was located on the left side of the image (L-target); in the other half of the scenes, the target was on the right side (R-target). To control for lef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The association between gaze bias and age was found for the first three to seven fixations in the horizontal dimension, and for the first to sixth fixations in the vertical dimension. Interestingly, previous studies have shown that in free viewing, a leftward bias is typically exhibited in these early fixations (Chiffi et al 2021 ; Foulsham et al 2018 ; Hartmann et al 2019 ; Nuthmann and Clark 2023 ; Nuthmann and Matthias 2014 ; Ossandon et al 2014 ). Such a gaze bias shortly after stimulus onset suggests that spatial attention is not biased per se, but that there is a bias in the spatial orienting of attention (as understood based on Petersen and Posner 2012 and Posner 1990 ).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The association between gaze bias and age was found for the first three to seven fixations in the horizontal dimension, and for the first to sixth fixations in the vertical dimension. Interestingly, previous studies have shown that in free viewing, a leftward bias is typically exhibited in these early fixations (Chiffi et al 2021 ; Foulsham et al 2018 ; Hartmann et al 2019 ; Nuthmann and Clark 2023 ; Nuthmann and Matthias 2014 ; Ossandon et al 2014 ). Such a gaze bias shortly after stimulus onset suggests that spatial attention is not biased per se, but that there is a bias in the spatial orienting of attention (as understood based on Petersen and Posner 2012 and Posner 1990 ).…”
Section: Discussionmentioning
confidence: 94%
“…This leftward bias peaks around the second to third fixation and persists for up to 1.5 s of a trial (Chiffi et al 2021 ; Foulsham et al 2018 ; Hartmann et al 2019 ; Ossandon et al 2014 ). This leftward gaze bias is robust to stimulus content (Ossandon et al 2014 ), viewing distance (Hartmann et al 2019 ), and even task goals such as visual search or memorization (Nuthmann and Clark 2023 ; Nuthmann and Matthias 2014 ; Zelinksy 1996 ). Furthermore, the bias remains present when there is no need to maintain central fixation before image onset, ruling out explanations related to asymmetries in fixation control (Ossandon et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…This bias also manifests itself in eye movements, where the first saccade on a face is often aimed towards the left (Butler et al, 2005;Butler & Harvey, 2006;Hsiao & Cottrell, 2008;Mertens et al, 1993). Notably, however, some of this effect may not be specific to faces, but may reflect a more general tendency to direct the first saccade on complex stimuli towards the left (e.g., for natural scenes see Nuthmann & Clark, 2023;Nuthmann & Matthias, 2014), a phenomenon which has been hypothesized to reflect a relative dominance of right-hemispheric parietal-frontal attention networks ("pseudoneglect"; Bowers & Heilman, 1980). Regardless of the exact cause of this leftward bias, we interestingly observed that it was already present for microsaccades during the prestimulus baseline interval (see Fig.…”
Section: Stereotypical Saccades Within the Face Were Found In Nearly ...mentioning
confidence: 99%